Extended tanh-function method for finding travelling wave solutions of some nonlinear partial differential equations - İnç, Mustafa; Fan, EG (Walter de Gruyter Gmbh, 2005)
In this paper, we find travelling wave solutions of some nonlinear partial differential equations (PDEs) by using the extended tanh-function method. Some illustrative equations are investigated by this method and new travelling wave solutions are found. In addition, the properties of these nonlinear PDEs are shown with some figures.
Keywords: tanh-function method; nonlinear PDEs; travelling wave solution; symbolic computation